Effect Of Ownership Structure On Company Value With Leverage Mediation (Studies In Manufacturing Companies That Listed On The Indonesia Stock Exchange) - Sri Adji Prabawa (The Manager Review, 2023)
Abstract: This research aims to test and analyze the impact of ownership structure on value of the firm and mediated by leverage in one integrated research model of the manufacturing company of the basic and chemical industry sectors listed on the Indonesia Stock Exchange in 2012-2018. Using a regression analysis tool and a Sobel test to see if the ownership structure has an indirect impact on the value of the firm. The results showed there was a significant negative influence of ownership structures on the company's value. Results also showed significant negative influence over the ownership structure on the leverage, and there was a significant positive influence of leverage on the company's value. The results of Sobel test showed that the leverage variable did not act to impact the indirect relationship of the ownership structure on the company's value. Keywords: Ownership Structure, Leverage, Value of the Firms. Abstrak: Penelitian ini bertujuan untuk menguji dan menganalisis pengaruh struktur kepemilikan terhadap nilai perusahaan dan dimediasi oleh leverage dalam satu model penelitian terpadu pada perusahaan manufaktur sektor industri dasar dan kimia yang terdaftar di Bursa Efek Indonesia tahun 2012-2018. Menggunakan alat analisis regresi dan uji Sobel untuk melihat apakah struktur kepemilikan memiliki dampak tidak langsung terhadap nilai perusahaan. Hasil penelitian menunjukkan terdapat pengaruh negatif signifikan struktur kepemilikan terhadap nilai perusahaan. Hasil penelitian juga menunjukkan pengaruh negatif signifikan struktur kepemilikan terhadap leverage, dan terdapat pengaruh positif signifikan leverage terhadap nilai perusahaan. Hasil uji Sobel menunjukkan bahwa variabel leverage tidak berpengaruh terhadap hubungan tidak langsung struktur kepemilikan terhadap nilai perusahaan. Kata kunci: Struktur Kepemilikan, Leverage, Nilai Perusahaan.